Clinical Signs in Allergic Rhinitis Patients at Dr. Hasan Sadikin General Hospital Bandung 2017-2021 - Exel Billy Wibowo; Arif Dermawan; Melati Sudiro (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The clinical diagnosis of allergic rhinitis requires comprehensive data from the history and physical examination. Despite being a substantial component of the diagnosis for allergic rhinitis, there is a paucity of studies about clinical signs of allergic rhinitis in Indonesia. This study aimed to describe the clinical signs in allergic rhinitis patients at Dr. Hasan Sadikin General Hospital Bandung.Methods: This cross-sectional study was conducted at Dr. Hasan Sadikin General Hospital Bandung in 2021, including secondary data of patients with allergic rhinitis from medical records registered from 2017 to 2021. Data of the characteristics, clinical signs, and allergic rhinitis comorbidities were collected and presented in tables.Results: The most common clinical sign was turbinate hypertrophy (74%), followed by pale nasal mucosa (59%) and clear nasal discharge (59%). The most prevalent comorbidities were chronic rhinosinusitis, adenoid hypertrophy, and asthma.Conclusions: The clinical signs observed from allergic rhinitis patients may vary, with the most common findings, including nasal turbinate hypertrophy, pale nasal mucosa, and clear nasal discharge. The findings may help the clinicians to diagnose allergic rhinitis needed for therapy management.